Key genetic elements, single and in clusters, underlying geographically dependent SARS-CoV-2 genetic adaptation and their impact on binding affinity for drugs and immune control. (30th November 2020) - Salpini, Romina; Alkhatib, Mohammad; Costa, Giosuè; Piermatteo, Lorenzo; Ambrosio, Francesca Alessandra; Di Maio, Velia Chiara; Scutari, Rossana; Duca, Leonardo; Berno, Giulia; Fabeni, Lavinia; Alcaro, Stefano; Ceccherini-Silberstein, Francesca; et al.
Abstract: Objectives: To define key genetic elements, single or in clusters, underlying SARS-CoV-2 (severe acute respiratory syndrome coronavirus-2) evolutionary diversification across continents, and their impact on drug-binding affinity and viral antigenicity. Methods: A total of 12 150 SARS-CoV-2 sequences (publicly available) from 69 countries were analysed. Mutational clusters were assessed by hierarchical clustering. Structure-based virtual screening (SBVS) was used to select the best inhibitors of 3-chymotrypsin-like protease (3CL-Pr) and RNA-dependent RNA polymerase (RdRp) among the FDA-approved drugs and to evaluate the impact of mutations on binding affinity of these drugs. The impact of mutations on epitope recognition was predicted following Grifoni et al . ( Cell Host Microbe 2020; 27: 671–80.) Results: Thirty-five key mutations were identified (prevalence: ≥0.5%), residing in different viral proteins. Sixteen out of 35 formed tight clusters involving multiple SARS-CoV-2 proteins, highlighting intergenic co-evolution. Some clusters (including D614GSpike + P323LRdRp + R203KN + G204RN ) occurred in all continents, while others showed a geographically restricted circulation (T1198KPL-Pr + P13LN + A97VRdRp in Asia, L84SORF-8 + S197LN in Europe, Y541CHel + H504CHel + L84SORF-8 in America and Oceania). SBVS identified 20 best RdRp inhibitors and 21 best 3CL-Pr inhibitors belonging to different drug classes. Notably, mutations in RdRp or 3CL-Pr modulate, positively or negatively, the binding affinity of these drugs. Among them, P323LRdRp (prevalence: 61.9%) reduced the binding affinity of specific compounds including remdesivir while it increased the binding affinity of the purine analogues penciclovir and tenofovir, suggesting potential hypersusceptibility. Finally, specific mutations (including Y541CHel + H504CHel ) strongly hampered recognition of Class I/II epitopes, while D614GSpike profoundly altered the structural stability of a recently identified B cell epitope target of neutralizing antibodies (amino acids 592–620). Conclusions: Key genetic elements reflect geographically dependent SARS-CoV-2 genetic adaptation, and may play a potential role in modulating drug susceptibility and hampering viral antigenicity. Thus, a close monitoring of SARS-CoV-2 mutational patterns is crucial to ensure the effectiveness of treatments and vaccines worldwide.